2012
DOI: 10.1590/s0100-06832012000600002
|View full text |Cite
|
Sign up to set email alerts
|

Carbono orgânico total, biomassa microbiana e atividade enzimática do solo de áreas agrícolas, florestais e pastagem no médio Vale do Paraíba do Sul (RJ)

Abstract: RESUMOCaracterísticas do solo, como o carbono orgânico total (COT), a biomassa microbiana e a atividade enzimática, são influenciadas por diversos fatores e têm sido apontadas como indicadores adequados de alterações provocadas por diferentes sistemas de uso e manejo do solo. O objetivo deste trabalho foi avaliar o COT, a biomassa microbiana e a atividade enzimática de um Cambissolo Háplico Tb distrófico típico de áreas agrícolas, florestais e de pastagem, no Médio Vale do Paraíba do Sul (RJ). Os sistemas aval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
38
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 29 publications
12
38
0
13
Order By: Relevance
“…Similar MBCs between native forest and pasture areas were also found in studies carried out in São Paulo (Marchiori Júnior and Mello, 1999) and Rio de Janeiro (Silva et al, 2012a).…”
Section: Carbon and Microbial Biomass Activitysupporting
confidence: 83%
See 1 more Smart Citation
“…Similar MBCs between native forest and pasture areas were also found in studies carried out in São Paulo (Marchiori Júnior and Mello, 1999) and Rio de Janeiro (Silva et al, 2012a).…”
Section: Carbon and Microbial Biomass Activitysupporting
confidence: 83%
“…These practices can affect ecosystem equilibrium and the chemical, physical, and biological properties of soil, which can be considered indicators of environmental degradation and recovery (Machado et al, 2010;Silva et al, 2012a;Guareschi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although there was no significant difference in FDA between the dry and rainy seasons for the 50S:50E stands, there was a tendency toward higher values of total enzyme activity in the dry season, in which the highest C and N levels were observed. Silva et al (2012) found high correlations between the activity of different enzymes (β-glucosidase, arylsulfatase, and acid phosphatase) and C in soils of forest systems at different stages of succession. The higher FDA activity in the 100E plantation and respiration in the 100S plantation in the dry season may be related to greater litter deposition rates at that time, which can stimulate microbial activity.…”
Section: Discussionmentioning
confidence: 93%
“…The authors claim that FDA activity represents the heterotrophic potential of Rev Bras Cienc Solo 2017;41:e0160239 soils because it represents the activity of enzyme groups that decompose organic matter (Dick et al, 1996). Other studies (Evangelista et al, 2012;Silva et al, 2012) have shown that the activity of several enzymes is influenced by the levels of organic matter in soils.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation